Benchmarking the Technical Efficiency of South African Municipal Water Utilities: A Double-Bootstrap Dea Approach - Matutu, Amanda (University of the Witwatersrand, Johannesburg, 2023)
Efficiency enhancement in the water sector can help to optimise the use of available resources and mitigate the impact of climate change on water resources, while promoting sustainable water usage. Ultimately, this can lead to cost savings that may be channelled into enhancing service delivery and expanding access to water. Benchmarking is considered a useful method for improving water sector efficiency. The production frontier approach is the most commonly used technique for benchmarking, which can be computed using either non-parametric techniques, including data envelopment analysis (DEA), or parametric methods, including stochastic frontier analysis (SFA). A review of the literature reveals that DEA has become the most frequently used method for efficiency analysis in the water sector. Though a predictable approach, the DEA method may be influenced by measurement errors and anomalies, and it cannot be used to draw statistical conclusions. To address this problem, the double-bootstrap DEA technique was introduced, which permits statistical inference in DEA models. This technique helps the researcher to estimate efficiency scores that have been corrected for bias, and also identifies the factors that influence efficiency. For these reasons, this research employs double-bootstrap DEA to evaluate the efficiency scores of municipal water utilities in the South African water sector. The truncated double-bootstrap regression outcomes show that water consumer debt, consuming units receiving free water, and the effects of climate change (such as temperature variation and altered rainfall patterns) all impact the relative efficiencies of municipal water utilities. The results indicate notable distinctions in rankings and efficiency scores between the double-bootstrap DEA model and the traditional DEA model for both urban and rural municipal water utilities. Using the regression model, this research discovered that water consumer debt and consuming units receiving free water are significant factors influencing the efficiency of urban and rural municipal water utilities. These findings raise concerns about the prospects of South African municipal water utilities, particularly their ability to strike a balance between supporting indigent households and securing revenue for maintenance and future water infrastructure development, as well as efficiently managing water consumer debt and addressing the effects of climate change to deliver desired results consistently and sustainably.
A Research Report submitted in partial fulfilment to the Faculty of Commerce, Law and Management, of the Degree of Master of Commerce (Economics – CCA01), in the School of Economics and Finance, University of the Witwatersrand, Johannesburg, in 2023.
Keywords: Benchmarking; Efficiency; Municipal water utilities; Data envelopment analysis; Double-bootstrap; Bias correction; UCTD; SDG-6: Clean water and sanitation